Design of Disc on Disc Wear Test Equipment Using VDI 2221 Method - Dedi Rosa Putra Cupu; Nandha Syamza (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2021)
This study aims to design the build of a wear test tool or a tribometer that intends to measure the coefficient of friction and wear rate in contact materials in form of disc-on-disc. This tribometer test tool can be used in dry contact (without any intermediate material between contacts) or wet contacts (by using intermediate material between contacts such as lubricant). The application of this disc-on-disc type of tribometer is the contact that occurs between roller elements (solid cylinders) and inner rings on cylindrical rolling bearings. In this paper is used the design method of VDI 2221. The steps are to clarify the task, determine the function of structure, look for the principle of the solution and its structure, describe the variants that can be realized and give shape to the model and detail the manufacture and used. This tool is used to test components consisting of two discs where the material can be varied. The design of the surface contact side mechanism is done in a radial direction. So, the disc can rotate (rolling contact) and this test tool can be varied load and rotation. The final result of this study is an engineering document in the form of layout drawings and assembly images as well as detailed images of each component and bills of materials.